Business Model Canvas Sebagai Strategi Pengembangan Usaha pada UMKM Batik Bambu Kenanga di Kabupaten Malang - Rina Juliasari; Achmad Zaini; Ayu Sulasari (Indo Publishing, 2026)
During 2024 batik sales at UMKM Batik Bambu Kenanga experienced unstable sales and limitations in online sales through whatsapp and offline sales with limited use of digitalization. This research aims to design a Business Model Canvas (BMC) as strategic decision making in formulating business development strategies at UMKM Batik Bambu Kenanga. The main focus of this research is limited to business development through the Channels element, which includes distribution and promotion channels both offline and online. The data collection process uses a qualitative approach with a case study method that includes interviews, observations, and documentation with owners and employees. The research results that the Business Model Canvas (BMC) design has succeeded in describing the real conditions of the UMKM Batik Bambu Kenanga through nine main elements. The business development strategy formulated from the BMC design results is focused on the Channels element and is divided into two stages, namely short-term and long-term strategies. The use of Business Model Canvas as an analysis and strategy development tool has proven to be effective in helping UMKM Batik Bambu Kenanga formulate business development steps that are more adaptive, structured, and sustainable.